2013
DOI: 10.1098/rspb.2013.1680
|View full text |Cite
|
Sign up to set email alerts
|

Food vibrations: Asian spice sets lips trembling

Abstract: Szechuan pepper, a widely used ingredient in the cuisine of many Asian countries, is known for the tingling sensation it induces on the tongue and lips. While the molecular mechanism by which Szechuan pepper activates tactile afferent fibres has been clarified, the tingling sensation itself has been less studied, and it remains unclear which fibres are responsible. We investigated the somatosensory perception of tingling in humans to identify the characteristic temporal frequency and compare this to the establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 39 publications
4
21
0
2
Order By: Relevance
“…Since the PC channel mechanoreceptor is absent in orofacial skin [2729], our aim of testing multiple channels suggested using the fingertips, rather than the lips. We therefore first confirmed that the tingling sensation by sanshool could be also reliably elicited on the finger, not only on the lips as it has been shown previously [7]. …”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Since the PC channel mechanoreceptor is absent in orofacial skin [2729], our aim of testing multiple channels suggested using the fingertips, rather than the lips. We therefore first confirmed that the tingling sensation by sanshool could be also reliably elicited on the finger, not only on the lips as it has been shown previously [7]. …”
Section: Resultssupporting
confidence: 87%
“…Since all of the participants reported the tingling sensation on the lips in the previous study [7], this result may be due to the individual differences in the skin thickness on the finger; for these two participants, the sanshool may have not reached the dermic layer to activate the receptors/fibres. Therefore, these two participants were excluded from the further experiments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations